Nd and Sr isotope compositions of different phases of surface sediments in the South Pacific: Extraction of seawater signatures, boundary exchange, and detrital/dust provenance. (2nd September 2014) - Molina‐Kescher, Mario; Frank, Martin; Hathorne, Ed C.
Abstract The radiogenic isotope composition of neodymium (Nd) and strontium (Sr) are useful tools to investigate present and past oceanic circulation or input of terrigenous material. We present Nd and Sr isotope compositions extracted from different sedimentary phases, including early diagenetic Fe‐Mn coatings, "unclean" foraminiferal shells, fossil fish teeth, and detritus of marine surface sediments (core‐tops) covering the entire midlatitude South Pacific. Comparison of detrital Nd isotope compositions to deep water values from the same locations suggests that "boundary exchange" has little influence on the Nd isotope composition of western South Pacific seawater. Concentrations of Rare Earth Elements (REE) and Al/Ca ratios of "unclean" planktonic foraminifera suggest that this phase is a reliable recorder of seawater Nd isotope composition. The signatures obtained from fish teeth and "nondecarbonated" leachates of bulk sediment Fe‐Mn oxyhydroxide coatings also agree with "unclean" foraminifera. Direct comparison of Nd isotope compositions extracted using these methods with seawater Nd isotope compositions is complicated by the low accumulation rates yielding radiocarbon ages of up to 24 kyr, thus mixing the signal of different ocean circulation modes. This suggests that different past seawater Nd isotope compositions have been integrated in authigenic sediments from regions with low sedimentation rates. Combined detrital Nd and Sr isotope signatures indicate a dominant role of the Westerly winds transporting lithogenic material from South New Zealand and Southeastern Australia to the open South Pacific. The proportion of this material decreases toward the east, where supply from the Andes increases and contributions from Antarctica cannot be ruled out.